Pathobiology of T-cell and NK-cell lymphomas - Bajor-Dattilo, Ewa B. (2013)
T-cell and NK-cell lymphomas are uncommon lymphomas with an aggressive clinical course. The causes and precise cellular origin of most T-cell lymphomas are still not well defined. The WHO classification utilizes morphologic and immunophenotypic features in conjunction with clinical aspects and in some instances genetics to delineate a prognostically and therapeutically meaningful categorization. The anatomic localization of neoplastic T-cells and NK-cells parallels in part their proposed normal cellular counterparts and functions. T-cells of the adaptive immune system are mainly based in lymph nodes and peripheral blood, whereas lymphomas derived from T-cells and NK-cells of the innate immune system are mainly extranodal. This approach allows for better understanding of some of the manifestations of the T-cell and NK-cell lymphomas, including their cellular distribution, some aspects of morphology and even associated clinical findings.